If one of the zeros of the quadratic polynomial (k-1) x2 + kx + 1 is -3, then find the value of k.

Given that P(x) = ( k -1 ) x² + kx + 1 = 0.

→ p( -3 ) = ( k – 1 ) (-3)² + k (-3) + 1 = 0.

⇒ ( k – 1 ) × 9 -3 k + 1 = 0.

⇒ 9k – 9 – 3k + 1 = 0.

⇒ 6k – 8 = 0.

⇒ 6k = 8.

Therefore, k = 8/6 = 4/3

Was this answer helpful?

  
   

4.5 (13)

Upvote (20)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question